State Domestic Product of Himachal Pradesh 1970-71 1978-79 - Planning Commission (Planning Commission, 1970)
Advent of Planning has brought the need for reliable key indicators of the level of development in socio- economic sectors. For assessing the growth in the structure and composition of regional economy from time to time and to visualise the functioning of the economic system as a whole, State Income estimates are one of the indicators.
Economic and Statistics, Himachal Pradesh